A novel engineered purified exosome product patch for tendon healing: An explant in an ex vivo model. Issue 8 (14th October 2020) - Shi, Guidong; Wang, Yicun; Wang, Zhanwen; Thoreson, Andrew R.; Jacobson, Daniel S.; Amadio, Peter C.; Behfar, Atta; Moran, Steven L.; Zhao, Chunfeng
Abstract: Reducing tendon failure after repair remains a challenge due to its poor intrinsic healing ability. The purpose of this study is to investigate the effect of a novel tissue‐engineered purified exosome product (PEP) patch on tendon healing in a canine ex vivo model. Lacerated flexor digitorum profundus (FDP) tendons from three canines' paws underwent simulated repair with Tisseel patch alone or biopotentiated with PEP. For the ex vivo model, FDP tendons were randomly divided into three groups: FDP tendon repair alone group (Control), Tisseel patch alone group, and the Tisseel plus PEP (TEPEP) patch group. Following 4 weeks of tissue culture, the failure load, stiffness, histology, and gene expression of the healing tendon were evaluated. Transmission electron microscopy revealed that in exosomes of PEP the diameters ranged from 93.70 to 124.65 nm, and the patch release test showed this TEPEP patch could stably release the extracellular vesicle over 2 weeks. The failure strength of the tendon in the TEPEP patch group was significantly higher than that of the Control group and Tisseel alone group. The results of histology showed that the TEPEP patch group had the smallest healing gap and the largest number of fibroblasts on the surface of the injured tendon. Quantitative reverse transcription polymerase chain reaction showed that TEPEP patch increased the expression of collagen type III, matrix metallopeptidase 2 (MMP2), MMP3, MMP14, and reduced the expression of transforming growth factor β1, interleukin 6. This study shows that the TEPEP patch could promote tendon repair by reducing gap formation and inflammatory response, increasing the activity of endogenous cells, and formation of type III collagen.